Penatalaksanaan Terapi Latihan Pada Kondisi Burst Frakture Vertebra Lumbal 1 Dengan Claudia Equina Syndrome Di Rso Prof. Dr. R. Soeharso Surakarta - Wibowo, Dwi Wahyu; , Totok Budi Santoso, S.Fis.,Ftr.,MPH (2015)
Background: Lumbal Vertebrae 1 Burst Fracture with Claudia Equina Syndrome is a fracture that occurs in the lumbal vertebrae, manifestations of this condition is the presence of pain in the hip area, causing a burst fracture VL1 with Claudia EquinaSyndrome has been known as trauma, osteoporosis and so on, although symptoms which happens not only are there too severe pain in the hip area, but needs good handling, in order to prevent the condition worsening. The purpose of the problem: The purpose of the problem of reducing pain on ADL areas, such as difficulty getting out of bed, walking, and activities of daily living. Methods: The method used in this scientific paper is a case study, using several instruments, among others, the examination pain studies with VDS Scale and Functional Capabilities with Kenny Self Care Index. To overcome these problems can be used modalities such as exercise therapy. Results: After treatment modality as much as 6x with exercise therapy is as follows: T1 = silent pain is very mild pain, T6 = no pain, tenderness motion, T1 = severe pain at all, becomes T6 = mild pain, tenderness T1 = severe pain T6 = mild pain and an increase in functional ability were measured using Kenny Self-Care Index of the total value of T1 = 22 to T6 = 31. Conclusion: Patients can be helped and can follow the instructor using the physiotherapy modalities such as exercise therapy is deep breathing exercises, relaxed passive movement, free active exercise, static contraction, change position, and ambulation transfer can help reduce the problems caused by the burst fracture Lumbal Vertebra 1 by Claudia Equina Syndrome. Keywords: burst fracture of lumbal vertebrae 1, Clauda Equina Syndrome, exercise therapy